2006
DOI: 10.4049/jimmunol.177.2.814
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Th2-Mediated Allergic Airway Inflammatory Disease by CD137 Costimulation

Abstract: The engagement of CD137 (4-1BB), an inducible T cell costimulatory receptor and member of the TNF receptor superfamily, by agonistic Abs can promote strong tumor and viral immunity mediated by CD8+ T cells and stimulate IFN-γ production. However, its role in Th2-mediated immune responses has not been well defined. To address this issue, we studied the function of CD137 engagement using an allergic airway disease model in which the mice were sensitized with inactivated Schistosoma mansoni eggs followed by S. ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Whether any of these activities were due to a direct effect of signaling to the CD4 T cells is not known. Suppression of CD4 T cell reactivity by anti-4-1BB was also shown in mouse models of allergic asthma [53,54] accompanied by prevention of the development of disease as well as reversal of established disease. The protective function in this case was associated with a marked reduction of Th2 cytokines but augmented IFN-γ.…”
Section: Cd8+ Treg and Novel Immune Regulation From 4-1bbmentioning
confidence: 85%
“…Whether any of these activities were due to a direct effect of signaling to the CD4 T cells is not known. Suppression of CD4 T cell reactivity by anti-4-1BB was also shown in mouse models of allergic asthma [53,54] accompanied by prevention of the development of disease as well as reversal of established disease. The protective function in this case was associated with a marked reduction of Th2 cytokines but augmented IFN-γ.…”
Section: Cd8+ Treg and Novel Immune Regulation From 4-1bbmentioning
confidence: 85%
“…It is possible that a deficiency in 4-1BBL/4-1BB signalling (including s4-1BBL) may contribute to a shift from a T h 1 response to a T h 2 response in asthma. 32 As such, the decrease in 4-1BBL might promote the development of allergic asthma. A T h 17/T reg imbalance has been shown to be present in patients with asthma, particularly in moderate-to-severe disease.…”
mentioning
confidence: 99%
“…Early observations showed that the same agonistic mAb to CD137 that have a potent anti-tumor effect (Melero et al, 1997) can abrogate T celldependent Ab responses (Mittler et al, 1999). Since this phenomenon was reported, an explosion of literature have demonstrated that stimulation of CD137 results in strong suppression of a variety of autoimmune or inflammatory diseases that are believed to be mediated mainly by CD4 + T cells (Sun et al, 2002a(Sun et al, , 2002b(Sun et al, , 2006Foell et al, 2003Foell et al, , 2004Seo et al, 2004;Fukushima et al, 2005;Kim et al, 2005Kim et al, , 2007Shao et al, 2005;Cho et al, 2006;Polte et al, 2006). Mechanisms of action behind anti-CD137-mediated immunosuppression still remain to be fully elucidated but seem to depend upon the context of inflammatory processes involved in the development of diseases.…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 99%
“…For example, agonistic anti-CD137 mAb inhibits autoantibody production almost without exception, subsequently blocking autoantibody-mediated autoimmune diseases such as SLE and rheumatoid arthritis (Sun et al, 2002b;Foell et al, 2003Foell et al, , 2004Seo et al, 2004;Kim et al, 2005). CD137 ligation also serves as a powerful therapeutic mediator for Th2-mediated diseases, including asthma (Fukushima et al, 2005;Cho et al, 2006;Polte et al, 2006;Sun et al, 2006). By contrast, agonistic anti-CD137 mAb exacerbates diseases accompanying acute inflammation (Kim et al, 2009).…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 99%
See 1 more Smart Citation